Mysticism and Preaching on the Madurese Folk Arts Stage in Indonesia: The Other Side of Islam - Burhanudin, Dede; Aripudin, Acep (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The rise and advancement of traditional arts in Indonesia is linked to the spread of Islam. This is evident in how Islam was introduced to Madura Island. The artworks of religious communities do not always follow the logical progression of their core beliefs. In traditional communities, art can elevate community morale and serve as a vehicle for religious dissemination. Art can also be a productive medium. Art and religious culture are inherently functionally connected when cultural values ​​in art are combined and integrated into a mutually supportive regional wisdom. Within this framework, this paper seeks to explain the functional relationship between Islamic religious principles and the creative traditions of the Madurese people. The sacred position of religion and the profane status of art can shift. The relationship between Islam and art can be seen in song lyrics, the history of artistic creation, historical moments in art, art genres, religious expansion, and the authority of religious leaders. Ultimately, Islamic ideas are preserved alongside the traditional arts of the community and eventually develop into a multifaceted force that supports the local economy.